Analisis Pendapatan dan Prospek Pemasaran pada Wirausahawan Fried Chicken di Kota Kendari: Analysis of Income And Marketing Prospects of Fried Chicken Entrepreneurs in Kendari City - Laode Muh Munadi; Nuraini Nuraini; La Ode Muh Munadi; Githaria Lumanto (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
Abstract The best known broiler chicken meat product in urban communities is Kentucky Fried Chicken (KFC). Seeing the business opportunity, entrepreneurs in Kendari City tried to make fried chicken similar to KFC products by labeling Kendari Fried Chicken (Kendari-FC) at a relatively affordable price of Rp 8.000 per piece compared to the KFC price of Rp 15.000 per piece. This study aims to analyze the marketing prospects of Kendari-FC entrepreneurs in Kendari City. The location of the research was determined purposively with the respondents of the study being kendari-FC entrepreneurs in kendari city who were determined by census. The results showed that the income of Kendari-FC entrepreneurs in Kendari City averaged Rp 5.066.458 per month or Rp 168.882 per day with an average income of Rp 36.276 per head. Kendari-FC's marketing prospects have the potential to be developed especially in West Kendari District because the average revenue from sales of each tail is Rp 48.105.40 per head. Keywords: Income; Kendari-FC; Marketing Abstrak Produk hasil olahan daging ayam broiler yang paling dikenal masyarakat perkotaan adalah Kentucky Fried Chicken (KFC). Melihat peluang bisnis tersebut wirausahawan di Kota Kendari berupaya membuat ayam goreng yang mirip produk KFC dengan memberi label Kendari Fried Chicken (Kendari-FC) dengan harga relatif terjangkau yaitu Rp 8.000 per potong dibandingkan harga KFC Rp 15.000 per potong. Penelitian ini bertujuan menganalisis prospek pemasaran wirausaha Kendari-FC di Kota Kendari. Lokasi penelitian ditentukan secara purposif dengan responden penelitian adalah wirausahawan Kendari-FC di Kota Kendari yang ditentukan secara sensus. Hasil penelitian menunjukan bahwa pendapatan wirausahawan Kendari-FC di Kota Kendari rata-rata Rp 5.066.458 per bulan atau Rp 168.882 per hari dengan pendapatan rata-rata Rp 36.276 per ekor. Prospek pemasaran Kendari-FC berpotensi dikembangkan terutama di Kecamatan Kendari Barat karena rata-rata pendapatan dari hasil penjualan setiap ekor sebesar Rp 48.105.40. Kata kunci: Kendari-FC; Pemasaran; Pendapatan